1982
DOI: 10.1021/jm00351a020
|View full text |Cite
|
Sign up to set email alerts
|

Analogs of 3-quinuclidinyl benzilate

Abstract: A number of analogues of 3-quinuclidinyl benzilate (QNB) have been synthesized and their affinities to muscarinic receptor from rat or dog ventricular muscle measured. We have determined that the muscarinic receptor can to a different degree accommodate either a halogen in the ortho, meta, or para position of one phenyl ring or the replacement of one phenyl ring with an alkyl group. Our in vitro competition studies show that the affinities lie within a 270-fold range, from the highest affinity compound, 3-quin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

1983
1983
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 1 publication
0
15
0
2
Order By: Relevance
“…In general, the higher the dose, the quicker the subject reached incapacitation and the longer the subject remained incapacitated. Doubling the ID 50 dose significantly increased the D 50 . The researchers concluded that BZ and other glycolate esters showed a multiple compartment distribution with differing elimination rates.…”
Section: Ketchum (2012) (7)mentioning
confidence: 94%
See 4 more Smart Citations
“…In general, the higher the dose, the quicker the subject reached incapacitation and the longer the subject remained incapacitated. Doubling the ID 50 dose significantly increased the D 50 . The researchers concluded that BZ and other glycolate esters showed a multiple compartment distribution with differing elimination rates.…”
Section: Ketchum (2012) (7)mentioning
confidence: 94%
“…All of the compounds examined in this study were considered potent anticholinergic agents. The LD 50 and ED 50 for these compounds are shown below (Table 5). Compound 344 (2-thienyl derivative) was the most potent anticholinergic compound based on the ED 50 for inhibiting spasms induced by acetylcholine (Table 5).…”
Section: Abood Et Al (1959)mentioning
confidence: 99%
See 3 more Smart Citations